The potential toxic effects of chronic doxorubicin treatment on the rat pancreas and the role of ghrelin in this context - Scott, Kirsten Lee (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.